2018
DOI: 10.21010/ajid.v12i2.13
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Non-Influenza Viruses in Acute Respiratory Infections in Children Under Five-Year-Old in Cote D’ivoire (January – December 2013).

Abstract: Background:Influenza sentinel surveillance in Cote d’Ivoire showed that 70% of Acute Respiratory Infections (ARI) cases remained without etiology. This work aims to describe the epidemiological, clinical, and virological pattern of ARI that tested negative for influenza virus, in children under five years old.Materials and Methods:one thousand and fifty nine samples of patients presenting influenza Like Illness (ILI) or Severe Acute Respiratory Infections (SARI) symptoms were tested for other respiratory virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
4
6
0
Order By: Relevance
“…Equal total amounts of viruses and a similar prevalence of RSV and influenza viruses were detected when comparing with our results, but these studies, including some recent Senegalese studies, found significantly higher percentages of adenovirus, enterovirus, and rhinovirus. 14,15,35,36 Results from case-control studies conducted in low-and middle-income countries show a similar prevalence of all viruses in healthy children, except that the average prevalence of rhinovirus in those studies is approximately 30%, whereas we found rhinovirus in 7.4% of controls. 19,[21][22][23][24] The most obvious possible reason for the differences in virus prevalence is our short study period, given that virus prevalence is highly seasonal.…”
Section: Discussionsupporting
confidence: 60%
“…Equal total amounts of viruses and a similar prevalence of RSV and influenza viruses were detected when comparing with our results, but these studies, including some recent Senegalese studies, found significantly higher percentages of adenovirus, enterovirus, and rhinovirus. 14,15,35,36 Results from case-control studies conducted in low-and middle-income countries show a similar prevalence of all viruses in healthy children, except that the average prevalence of rhinovirus in those studies is approximately 30%, whereas we found rhinovirus in 7.4% of controls. 19,[21][22][23][24] The most obvious possible reason for the differences in virus prevalence is our short study period, given that virus prevalence is highly seasonal.…”
Section: Discussionsupporting
confidence: 60%
“…Metapneumoviruses were also detected in a considerable proportions (6%) with transmission occurring mostly during the dry and cold seasons of the year. The prevalence was similar to that reported in a study conducted in the same region [33]. Previous studies have reported that hMPV was prevalent during late winter and spring in temperate climates [43, 44], but in our study, metapneumovirus was detected year‐long although peak transmission period coincided with pattern already described by other studies [43, 44].…”
Section: Discussionsupporting
confidence: 91%
“…Metapneumoviruses were also detected in a considerable proportions (6%) with transmission occurring mostly during the dry and cold seasons of the year. The prevalence was similar to that reported in a study conducted in the same region [33].…”
Section: Detected Pathogenssupporting
confidence: 89%
“…Thirteen of the studies used a WHO clinical classification of pneumonia 40 or SARI, 6,14,[17][18][19][20]25,29,32,36,39,41,42 while 3 South African studies in addition to children fulfilling the SARI definition also included any child under 3 months of age hospitalized for suspected infection. 5,25,33 The remaining 14 studies had varying case definitions of LRTI.…”
Section: Resultsmentioning
confidence: 99%